OVERVIEW OF CINNAMON BOILED WATER ADMINISTRATION TO SUPPORT PERINEAL WOUND HEALING IN MRS. S G2P2A0 POSTPARTUM DAY 4 IN JETIS VILLAGE - Nanda Cindi Dwi Karisma; Priyatin Sulistyowati; Dwi Astuti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background:Perineal rupture is a condition in which the perineal tissue tears during the childbirth process. This condition can cause pain, discomfort, and interfere with the mother’s activities after delivery. One non-pharmacological intervention that can support perineal wound healing is the administration of cinnamon boiled water. Cinnamon contains active compounds such as polyphenols, coumarin, and flavonoids, which possess antioxidant and anti-inflammatory properties, thus potentially accelerating the wound healing process. Objective:This study aims to describe the administration of cinnamon boiled water in supporting the healing of perineal wounds among postpartum mothers in Jetis Village. Method:This scientific paper uses a descriptive research method with a case study approach. Results:The results showed a decrease in the degree of perineal wound after the administration of cinnamon boiled water. Conclusion: Based on the case study conducted over seven days, the administration of cinnamon boiled water to postpartum mothers can help accelerate the healing of perineal wounds.